The Influence of Environmental Accounting, Green Human Resource Accounting, and ESG Orientation on the Sustainable Performance of Manufacturing Companies - Mekar Meilisa Amalia (West Science Social and Humanities Studies, 2026)
This study examines the influence of Environmental Accounting (EA), Green Human Resource Accounting (GHRA), and Environmental, Social, and Governance (ESG) Orientation on the sustainable performance of manufacturing companies in Indonesia. Using a quantitative research design, data were collected from 125 manufacturing companies through a Likert scale-based survey. The data were analyzed using SPSS version 25, with multiple regression analysis conducted to assess the relationships between the independent variables (EA, GHRA, and ESG Orientation) and the dependent variable (Sustainable Performance). The findings reveal that all three practices—EA, GHRA, and ESG Orientation—have a significant positive impact on sustainable performance, with GHRA having the largest effect. The study highlights the importance of integrating environmental accounting, human resource practices, and ESG orientation into corporate strategies to enhance sustainability. The results provide valuable insights for policymakers and business leaders aiming to promote sustainable practices within the manufacturing sector in Indonesia.